2019
DOI: 10.1186/s12883-019-1435-y
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic conditioning improves cognition in patients with subcortical ischemic vascular dementia

Abstract: Background: Subcortical ischemic vascular dementia (SIVD) is very common among the older people, but has no approved treatment. Preclinical trials show that remote ischemic conditioning (RIC) reduces recurrence of ischemic stroke. We hypothesize that RIC may also be an effective therapy for patients with SIVD. Methods: Thirty-seven consecutive SIVD cases were enrolled in this randomized control study. Eighteen RIC patients underwent five brief cycles of conditioning (bilateral upper limb compression at 200 mmH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 31 publications
(35 reference statements)
0
24
0
Order By: Relevance
“…RIC has also been used widely in other contexts ( 36 ), including reduction of myocardial injury after ischemia in large animal models and human trials ( 37 ). In studies of cerebral pathologies, RIC has improved cognition in patients with subcortical ischemic vascular dementia ( 38 ) and conferred neuroprotective effects after acute ischemic stroke ( 39 ). It offered neuroprotection through enhanced cerebral perfusion, cerebral collateral formation, and tolerance of cerebral ischemia ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…RIC has also been used widely in other contexts ( 36 ), including reduction of myocardial injury after ischemia in large animal models and human trials ( 37 ). In studies of cerebral pathologies, RIC has improved cognition in patients with subcortical ischemic vascular dementia ( 38 ) and conferred neuroprotective effects after acute ischemic stroke ( 39 ). It offered neuroprotection through enhanced cerebral perfusion, cerebral collateral formation, and tolerance of cerebral ischemia ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] In addition, long-term daily RIC was effective in preventing new cerebral vascular lesions in patients with vascular dementia as well as patients with intracranial arterial stenosis. 19,48,55 However, strong evidence supporting the efficacy of RIC as a neuroprotective adjunct to thrombolysis/thrombectomy in AIS is still missing, and no clinical studies investigating potential benefits of RIC have targeted the ICH population specifically.…”
Section: Discussionmentioning
confidence: 99%
“…No patients experienced new ischemic or bleeding events during the treatment period. 48 Large vessel disease with atherosclerotic stenosis of preor intracerebral arteries is a major cause of stroke. 24,49 Carotid endarterectomy performed within 15 days of AIS/TIA is superior to best medical management in reducing stroke recurrence in patients with significant ipsilateral carotid artery stenosis.…”
Section: Remote Ischemic Conditioning In Stroke Preventionmentioning
confidence: 99%
“…Liao et al [74] found that remote ischemic conditioning was effective and safe to improve cognitive function in patients with subcortical ischemic vascular dementia. Tang et al [75] showed that computerized cognitive training significantly improved global cognitive function in patients with subcortical vascular cognitive impairment.…”
Section: Other Relevant Findingsmentioning
confidence: 99%